Voice-Driven C2: A Multilingual Generative AI System for Real-Time Geospatial Interaction in Military Operations - Paweł PIECZONKA; Marcin KUKIEŁKA (Communications of International Proceedings, 2025)
This paper presents the concept of an innovative Command and Control (C2) system for exploring digital multilayer maps with voice commands, using generative artificial intelligence and modern data science methods. The goal of the system is to accelerate decision-making within the Observe-Orient-Decide-Act (OODA) loop by transforming naturally spoken commands into actions on digital maps. The proposed system allows users to query terrain and objects, calculate distances and plan optimal routes, and overlay dynamic operational layers (e.g., weather, logistics, intelligence) - all in real time using voice commands. The solution is multilingual, scalable and field-ready, and its architecture ensures integration with existing NATO C2 data infrastructures and processes. Special emphasis has been placed on interoperability, security and speed. The use of a voice interface is expected to increase operators' situational awareness, reduce cognitive load and significantly accelerate key decision-making in dynamic operational conditions.
Keywords: Voice-controlled C2 systems; Generative AI in defense; NLP; GEOINT; OODA loop optimization